Analysis of in vivo absorption of didanosine tablets in male adult dogs by HPLC - PatrÃcia Severino; Heloisa Silva; Eliana B. Souto; Maria Helena A. Santana; Teresa Cristina T. Dalla Costa (Elsevier, 2012)
Didanosine is an effective antiviral drug in untreated and antiretroviral therapy-experienced patients with Human Immunodeficiency Virus (HIV). An automated system using on-line solid extraction and High Performance Liquid Chromatography (HPLC) with ultraviolet (UV) detection was developed and validated for pharmacokinetic analysis of didanosine in dog plasma. Modifications were introduced on a previous methodology for simultaneous analysis of antiretroviral drugs in human plasma. Extraction was carried out on C18 cartridges, with high extraction yield as stationary phase, whereas mobile phase consisted of a mixture of 0.02 M potassium phosphate buffer, acetonitrile (KH2PO4: acetonitrile: 96:4, v/v) and 0.5% (w/v) of heptane sulphonic acid. The pH was adjusted to 6.5 with triethylamine. All samples and standard solutions were chromatographed at 28Â Â°C. For an isocratic run, the flux was 1.0Â mL/min, detection was at 250Â nm and injected volume was 20Â Î¼L. The method was selective and linear for concentrations between 50 and 5000Â ng/mL. Drug stability data ranged from 96% to 98%, and limit of quantification was 25Â ng/mL. Extraction yield was up to 95%. Drug stability in dog plasma was kept frozen at â20Â Â°C for one month after three freezeâthaw cycles, and for 24Â h after processing in the auto sampler. Assay was successfully applied to measure didanosine concentrations in plasma dogs. Keywords: Didanosine, On-line solid phase extraction, HPLC, Male dogs